Congo Inc. : Bismarck's Testament - Bofane, In Koli Jean, 1954- (Book collections on Project MUSE., 2018)
"To the sound of machine gun fire and the smell of burning flesh, award-winning author In Koli Jean Bofane leads readers on a perilous, satirical journey through the civil conflict and political instability that have been the logical outcome of generations of rapacious multinational corporate activity, corrupt governance, widespread civil conflict, human rights abuses, and environmental degradation in Africa. Isookanga, a Congolese Pygmy, grows up in a small village with big dreams of becoming rich. His vision of the world is shaped by his exploits in Raging Trade, an online game where he seizes control of the world's natural resources by any means possible: high-tech weaponry, slavery, and even genocide. Isookanga leaves his sleepy village to make his fortune in the pulsating capital Kinshasa, where he joins forces with street children, warlords, and a Chinese victim of globalization in this blistering novel about capitalism, colonialism, and the world haunted by the ghosts of Bismarck and Leopold II. Told with just enough levity to make it truly heartbreaking, Congo Inc. is a searing tale about ecological, political, and economic failure."--